Pengaruh Brand Awareness Dan Inovasi Produk terhadap Keputusan Pembelian melalui Minat Beli sebagai Variabel Mediasi : (Studi Kasus Kedai Kopi KULO) - Kevin Kristianto; Noventia Karina Putri; Henry Casandra Gultom (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This study aims to analyze the influence of brand awareness and product innovation on purchase decisions, with purchase intention as a mediating variable, among consumers of Kedai Kopi KULO. The research is motivated by the declining Top Brand Index of Kedai Kopi KULO over the past five years, indicating a potential drop in purchase decisions due to weak brand awareness and limited product innovation. A quantitative approach was used, employing Partial Least Square Structural Equation Modeling (PLS-SEM) with the SmartPLS software. The results show that brand awareness does not have a direct and significant effect on purchase decisions, whereas product innovation has a positive and significant effect. Furthermore, both brand awareness and product innovation positively and significantly influence purchase intention, which in turn significantly mediates their effect on purchase decisions. These findings indicate that purchase intention plays a crucial role in bridging the influence of brand awareness and product innovation on consumers’ purchase decisions. Therefore, businesses should focus on enhancing product innovation strategies and increasing consumer purchase intention, along with building strong brand awareness, to improve purchase decisions and maintain competitiveness in an increasingly saturated market.